On hourly prediction of PM2.5 using spatial–temporal graph convolutional network - Ren, Zhenxing; Ji, Xinxin (Earth science informatics, 2025)
Globally, air pollution has garnered significant attention in the past few years. Accurate air pollution like PM 2.5 hourly prediction is an essential instrument for air protection because it can be utilized in developing air pollution prevention and control techniques and provides an early warning system for dangerous air pollutants. Conventional forecasting models are limited due to the extraction of spatial and spatiotemporal features between variables, emphasizing more on the temporal characteristics of the variables. Considering the spatiotemporal correlation of air pollution, we propose a novel hourly prediction model ICEEMDAN-SSA-VMD-ABSTGCN. Initially, the improved complete ensemble empirical mode decomposition with adaptive noise (ICEEMDAN) approach is utilized for the decomposition of observed PM 2.5 concentrations. Variational mode decomposition (VMD) is then leveraged to further decompose the selected signals with the highest multi-scale permutation entropy (MPE) after its parameters have been optimized using the sparrow search algorithm (SSA). Next, an attention-based spatial–temporal graph convolutional network (ABSTGCN) was built by merging several effect factors, such as air pollution factors, and meteorological data. This methodology can be used for concentration forecasting of PM 2.5 in the future.